1999
DOI: 10.2307/1387607
|View full text |Cite
|
Sign up to set email alerts
|

Specifying Intrusive Demands and Their Outcomes in Congregational Ministry: A Report on the Ministry Demands Inventory

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
53
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 29 publications
(25 reference statements)
3
53
0
Order By: Relevance
“…The criticism subscales, however, showed marginal to unacceptable levels of reliability, ranging from 0.05 to 0.64, and were dropped from the analysis. Composite measures of demand frequency and impact, aggregating the four subscales, showed good internal consistency, as found in the previous study by Lee (1999) above. Alphas for the present sample ranged from 0.84 to 0.86 for both pastors and their wives.…”
Section: Methodssupporting
confidence: 83%
See 3 more Smart Citations
“…The criticism subscales, however, showed marginal to unacceptable levels of reliability, ranging from 0.05 to 0.64, and were dropped from the analysis. Composite measures of demand frequency and impact, aggregating the four subscales, showed good internal consistency, as found in the previous study by Lee (1999) above. Alphas for the present sample ranged from 0.84 to 0.86 for both pastors and their wives.…”
Section: Methodssupporting
confidence: 83%
“…Lee (1999) reported alpha coefficients ranging from 0.49 (for the impact of family criticism) to 0.80 (for the frequency of personal criticism) across the eight frequency and impact subscales. Global measures of demand frequency and impact, aggregating the four types of demand, were more internally consistent, at alphas of 0.82 for both scales.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, these pastors typically have optimistic views of their church-based social networks, anticipating that members of their congregations could be counted on to offer emotional and material assistance if ever called upon. The latter finding is particularly interesting since most research has tended to view congregants more as sources of stress than sources of support (e.g., Han and Lee 2004;Lee 1999;Morris and Blanton 1998;Mueller and McDuff 2004). Indeed, there is only one previous study of which we are aware that analyzed the effects of social support from congregants, and that study found no significant association between congregational support and clergy's psychological well-being (Lee 2007).…”
Section: Discussionmentioning
confidence: 89%